Penerapan Pembelajaran Pendidikan Agama Islam Berbasis Multikultural di SMP Laksamana Martadinata Medan - Imam Setiawan; Junaidi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Multicultural values have become an integral part of the culture at Laksamana Martadinata Middle School Medan. Lots of success in cultivating and maintaining multicultural values is recognized as the result of learning Islamic Religious Education,especially for Muslim students at the school. This article uses descriptive research, which means a systematic, factual and accurate description of the facts, characteristics and relationships between the phenomena being investigated. Research shows that at Laksamana Martadinata Medan Middle School, a multicultural-based Islamic Religious Education learning approach hasbeen implemented successfully. Awareness of student diversity, both in terms of religion and culture, is the main basis for developing an inclusive learning approach. This school concretely aligns Islamic teachings with the values of multiculturalism in preparing learning materials. This material includes an understanding of tolerance, mutual respect, and celebrating religiousand cultural differences. This implementation has a positive impact on students, who become more open, understand diversity, and are able to develop inclusive attitudes.